Characterization and Phylogenetic Analysis of the Complete Mitochondrial Genome of Laelia suffusa (Lepidoptera: Erebidae, Lymantriinae). Issue 1 (11th January 2021) - Li, Jing; Lv, Qing; Zhang, Xiao-man; Han, Hui-lin; Zhang, Ai-bing
Abstract: In this study, the complete mitochondrial genome of a white tussock moth, Laelia suffusa (Walker, 1855) (Lepidoptera: Erebidae, Lymantriinae), was sequenced and annotated. The genome sequence was 15, 502 bp in length and comprised 13 PCGs, 2 rRNAs, 22 tRNAs, and a single noncoding control region (CR). The nucleotide composition of the genome was highly A + T biased, accounting for 79.04% of the whole genome and with a slightly positive AT skewness (0.015). Comparing the gene order with the basal species of Lepidoptera, a typical trnM rearrangement was detected in the mitogenome of L. suffusa . Besides, the trnM rearrangement was found at the head of trnI and trnQ, rather than at the back. The 13 PCGs used ATN as their start codons, except for the cox1 which used CGA. Out of the 22 tRNAs, only 1 tRNA ( trnS1 ) failed to fold in a typical cloverleaf secondary structure. The conserved motif 'ATAGA + poly-T' was detected at the start of the control region which was similar to other Lepidoptera species. In total, 10 overlapping regions and 19 intergenic spacers were identified, ranging from 1 to 41 and 2 to 73 bp, respectively. Phylogenetic analysis showed that Lymantriinae was a monophyletic group with a high support value and L. suffusa was closely related to tribe Orgyiini (Erebidae, Lymantriinae). Moreover, the phylogenetic relationship of Noctuoidea (Lepidoptera) species was reconstructed using two datasets (13 PCGs and 37 genes) and these supported the topology of (Notodontidae + (Erebidae + (Nolidae + (Euteliidae + Noctuidae)))).